The (LMD) System and the Comprehensive Quality Challenge in Algeria - Lamia Boukraa (Social Empowerment Journal, 2021)
Abstract: The LMD system is considered the latest reform that Algeria has witnessed in higher education, despite the partial reforms that intervened trying to fix it and reviewing the errors of its implementation and the problems that followed these mistakes. Algeria has set basic goals for its higher education by the implementation of this system, as its basis was to create quality in training, taking into account social demands and the requirements of the labor market in the process of running the educational process.         However, a closer look at the reality of higher education in Algeria shows that there are many and great challenges impeding its development and the performance of its roles towards society. Higher education, like other sectors, must have a strategy, a clear message, and applicable goals, so that this strategy serves the society and provides it with a human capital capable of leading the wheel of progress and granting it the future vision and solutions to reality problems and the best ways to achieve sustainable human development. In this article, we examine the extent to which the content and application of the (LMD) system are compatible with these latest comprehensive quality standards that guarantee higher education to fulfill its assigned roles to the fullest extent.